Perlindungan Hukum Nasabah Dalam Perjanjian Telemarketing Bank - Poernomo, Sri Lestari (UI Scholars Hub, 2019)
Telemarketing is one of the banking products. This research is conducted to analyze the validity of the agreement that was born and the offering of banking products through telemarketing, transactions made in telemarketing activities almost entirely do not fulfill the legal agreement requirements, namely contracts because if there are elements of oversight and fraud, the Bank must be responsible if a loss occurs because the bank uses customer data to be referenced to the insurance company that works with the bank. The problem examined is how the validity of the agreement that was born from bank telemarketing activities and the legal protection of its customers, which will be analyzed from theories related to contract law, consumer protection law and banking law, and the implementation and expected solutions